Coulomb blockade in ion-induced electron emission and neutralization mechanisms - Bajales Luna, Noelia (2007)
We present a time-dependent quantum mechanical calculation of the charge transfer process in He+ /Al collision, where the resonant neutralization to the ground and first excited states of He is taken into account in a correlated way according to a Coulomb blockade effect. Our results provide an explanation to the discrepancies still found between theory and experiments in low energy ion scattering for this system, as well as allow us to understand the presence of high energy electrons in ion induced secondary electron emission spectra.